Children's Rights and Family Autonomy in the South African Context: A Comment on Children's Rights Under the Final Constitution - Mosikatsana, Tshepo L. (1998)
This Article investigates the nature and extent of the protection granted to children's rights in the South African Constitution. It concludes that the child-centered approach of the Constitution entitles children, as independent actors, to certain fundamental rights. Acknowledging both the parent-centered nature of the existing South African legal framework and the entrenched support for practices, many rooted in indigenous law and tradition, that contribute to the oppression of children, the author argues that the constitutionalization of these rights will contribute to the betterment of children in South Africa, proving to be more than mere moral exhortation. Under apartheid in South Africa. children, who were treated only as objects of parental concern and not as independent actors, were left to the mercy of the state. As a result, they lost any claim to their fundamental rights. This Article argues that recognition of the inalienable rights of children, in fact and not just in the Constitution, is the critical step in improving children's lives and ensuring the future of a democratic South Africa. Specifically, constitutionalization provides a basis for challenging racially structured and parent-centered child welfare laws and practices